Lipoadenoma of parathyroid gland : report of a rare case - Ranjeetha Shenoy; Arun Behl; V Shantharam (Wolters Kluwer Medknow Publications, 2014)
Parathyroid adenoma is a rare disease. It is the most common cause of primary hyperparathyroidism. Patients are commonly mis-diagnosed and treated symptomatically rather than addressing the main cause. Parathyroid lipo-adenoma is a rare clinico-histological variant of parathyroid adenoma which owing to its bulky nature is found at aberrant locations and generally extends into the mediastinum, thus posing difficulty in diagnosis and surgical exploration. Here we present a young lady with classical signs and symptoms of primary hyper-parathyroidism who underwent excision of the single adenoma, and histologically was a lipoadenoma. This case report highlights the importance of appropriate pre-operative and intra-operative planning and execution for better recovery of the patients.